1997
DOI: 10.1007/s001340050336
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life 6 months after intensive care: results of a prospective multicenter study using a generic health status scale and a satisfaction scale

Abstract: Quality of life measured with a health-related quality of life scale and a satisfaction scale 6 months after an ICU stay depended on the admission diagnosis. Different dimensions of quality of life were variably affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
2
12

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 27 publications
7
65
2
12
Order By: Relevance
“…In the reference group the number of people that had pre-existing diseases was 3095 (51%) (data not shown). The most common pre-existing disease was psychiatric/abuse problems (15.7 %) as 12 indicated by the medical records. Importantly a lower percentage of these problems were indicated by the patient in the patient inquiry (p=0.001).…”
Section: Pre-existing Disease (Table 2 and 3)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the reference group the number of people that had pre-existing diseases was 3095 (51%) (data not shown). The most common pre-existing disease was psychiatric/abuse problems (15.7 %) as 12 indicated by the medical records. Importantly a lower percentage of these problems were indicated by the patient in the patient inquiry (p=0.001).…”
Section: Pre-existing Disease (Table 2 and 3)mentioning
confidence: 99%
“…The most important are age, (4)(5)(6)(7)(8) sex, (6,9) and intensive care-related factors such as APACHE II score, (5,10) admission diagnosis (11,12) and length of stay in the ICU. (8) In three recent studies we have found that pre-existing disease is a major contributor to a reduced HRQoL after critical care for reasons other than trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Em contrapartida à existência de vários trabalhos sobre condições de saúde e instrumentos de qualidade de vida em adultos 9 , poucos instrumentos são validados para uso em crianças 4 . A maioria destes mede apenas o grau de incapacidade em questões de reabilitação ou desenvolvimento.…”
Section: Introductionunclassified
“…Assessment of the level of patients' cognitive and functional impairment after a period of significant stress and of their potential need for help to reenter the family and social environments can both be of help to better understanding the repercussions of acute disease or trauma and of medical care. 8 While there are many studies of health condition and instruments for measuring quality of life in adults, 9 few instruments have been validated for use with children. 4 The majority of these only measure the degree of incapacity with questions on recovery or development.…”
Section: Introductionmentioning
confidence: 99%